The Analysis of Grammatical Errors In Advertisements On Instagram Social Media - Armayanti, Riska; Kamal, Alfiandy (English Literature Studi Program Universitas Islam Makassar, 2024)
This research aims to; analyze the types of English grammatical errors in advertisements on social media Instagram and what is the meaning of grammatical errors in advertisements on social media Instagram. This type of research is qualitative research using the Accommodation theory developed by Rod Ellis in 1999 which focuses on grammatical errors that occur in the process of learning a second or foreign language (Second Language Acquisition, SLA). This theory explains how second language learners overcome and correct their errors in grammar through the process of interaction and communication. The object of this research is English advertisements on social media Instagram. This research uses error analysis which is conducted in several stages. Preparation was done by selecting relevant advertisements from advertising accounts, after which the researcher took screenshots of the advertisements. Then, after the screenshots were taken, the data were analysed for identification and then classified into 3 categories namely omission, information error and sequencing error. The results of this research show that there are 3 types of errors that occur namely omission, misinformation, and misordering with a total of 15 data. There are omission 5, misinformation 3, and misordering 6. This research is expected to provide benefits for everyone especially for those who are interested in Applied Linguistics.